PENEMUAN MAKNA HIDUP PADA INSAN PASCA STROKE - Rachmawati, Adjeng Pudji (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2016)
Abstract — This study aims to potrayal of the meaning of life post-stroke human being. The process of the invention the meaning of life was divided into five stages: suffering phase, self-acceptance phase, meaning the discovery phase, meaning the realization phase, and meaningful life phase. In the discovery phase of the meaning of life in it contains the sourceof meaning in life in the form of creative values, experiental values, attitudinal values, and hopes values. In addition, it also discusses the factors that influence of post-stroke human beings find meaning in life. The approach used in this study is qualitative approach that aims to obtain a thorough and complete understanding of the cases. Data collected methodsused were observation and in-depth interviews. The study involved three people over the age of post-stroke human being 45-54 years who suffered paralysis as a research subject. Based on the results of the analysis showed that all three subjects suffer physically and mentally. But only two subjects who can change the condition of the suffering becomes meaningful appreciation of life. The existence of the values obtained from the sufferingbecomes an important source for the subject in the meaning of life. The implications of this study are expected, human beings can better interpret post-stroke life by doing activities that can support the healing process for the family and can continue to provide guidance and motivation to the human being in order to achieve post-stroke recovery. Abstrak — Penelitian ini bertujuan untuk melihat gambaran penemuan makna hidup pada insan pasca stroke. Proses penemuan makna hidup, tersusun ke dalam lima tahapan yaitu diawali tahap derita, tahap penerimaan diri, tahap penemuan makna, tahap realisasi makna, dan diakhiri tahap kehidupan bermakna. Selain itu dibahas pula mengenai faktor-faktor apa saja yang memengaruhi insan pasca stroke dalam menemukan makna hidup. Pendekatan yang digunakan pada penelitian ini adalah pendekatan kualitatif yang bertujuan untuk mendapatkan pemahaman secara menyeluruh dan utuh dari kasus yang ada. Metode pengumpulan data yang digunakan adalah observasi dan wawancara mendalam (depth-interview). Subjek pada penelitian ini melibatkan tiga orang insan pasca stroke yang berusia 45–54 tahun yang mengalami kelumpuhan. Berdasarkan hasil analisis yang diperoleh menunjukkan bahwa ketiga subjek mengalami penderitaan secara fisik dan mental. Tetapi hanya dua subjek yang dapat mengubah kondisi penderitaan tersebut menjadi penghayatan kehidupan yang bermakna (meaningfull). Adanya nilai-nilai yang diperoleh dari proses penderitaan menjadi sumber penting bagi subjek dalam menemukan makna hidup. Implikasi dari penelitian ini diharapkan, insan pasca stroke dapat lebih memaknai hidupnya dengan cara melakukan kegiatan yang dapat menunjang proses penyembuhan dan bagi keluarga dapat terus memberikan pendampingan dan motivasi kepada insan pasca stroke demi tercapainya kesembuhan.